DEVELOPMENT OF SUSTAINABILITY INDICATORS FOR MUSLIM FRIENDLY TOURISM IN MALAYSIA - Abdul Shukor, Syadiyah; Ahmad Bustamam, Ummi Salwa; Mohd Salikin, Norasikin; Anwar, Intan Fatimah; Nordin, Siti Nurulhuda; Mohamad Nor, Nur Shahira (I-iECONS e-proceedings, 2023)
Muslim friendly tourism is a tourism segment that adheres to the religious needs of Muslim tourists. It includes a wide range of services and facilities including transportation, restaurants, entertainment, and accommodations that designed for and directed at Muslims. Malaysia is one of the fastest growing countries in the Muslim friendly tourism industry sector, holding a sizeable market share. As sustainable tourism has emerged as the way forward for Muslim friendly tourism, specific sustainability indicators should be developed to be used in planning and decision-making of Muslim friendly tourism related matters. Yet, the majority of the existing sustainability indicators reflect other tourism niche such as ecotourism, small tourism enterprises, adventure tourism destinations, festival tourism, and ecological resort. Malaysia’s tourism industry contributed 12.8% to the gross domestic product (GDP) in 2021 and contributed 23.4% to the total employment. Hence, sustaining Muslim friendly tourism as a niche tourism segment is one of the country’s priorities. This study is on-going aims to develop sustainability indicators for Muslim friendly tourism in Malaysia. For this purpose, stage 1 of this research aims to identify sustainability indicators for Muslim friendly tourism and stage 2 aims to evaluate the relative importance of the indicators identified. Findings of this study is in line with the National Tourism Policy (2020-2030), which aiming to ensure the continuity of the country’s tourism industry and will support the Malaysian government specifically Ministry of Tourism, Arts and Culture (MOTAC) towards achieving Sustainable Development Goal (SDG) 8 on “decent work and economic growth” as tourism has the potential to contribute, directly or indirectly, to this goal.